Comparison of the effect of teaching games for understanding, sport education, combined and linear pedagogy on motor proficiency of children with developmental coordination disorder - Ghorbanzadeh, Behrouz; Kirazci, Sadettin; Badicu, Georgian (Frontiers in Psychology, 2024)
Introduction The prevalence of developmental coordination disorder (DCD) is increasing and it has been shown that the main problem of children with DCD is their low motor proficiency. Therefore, it is important to find a way to improve motor skills in these children. Thus, this study aimed to compare the effect of teaching games for understanding (TGFU), sport education (SE), combined (TGFU and SE), and linear pedagogy (LP) on motor proficiency of children with DCD. Methods In this regard, among 7-year-old children in Turkey, 80 children were selected voluntarily and by evaluating the MABCD-2 test. These children were randomly placed in four-LP (control), SE, TGFU, and combined (SE-TGFU) groups and practiced futsal exercises for 16 sessions under the supervision of coaches specific to each method. BOT-2 short-form test was used to evaluate motor proficiency. Results The results of the analysis of the covariance test showed that the group effect is significant, and the results of the post hoc LSD test showed a significant difference between the LP with SE, LP with TGFU, LP with combination, SE with TGFU, SE with combination and TGFU with combination groups (p = <0.001). Discussion Based on the results of this study, the combined method is the best compared to other methods. Generally, combining games as an important activity in childhood with SE that emphasizes improving the child’s self-esteem is a method that can solve the movement competence that is the main problem of DCD children and lead them to continue physical activity.